2021
DOI: 10.1101/2021.01.25.21250040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19-related disruptions to routine vaccination services in India: perspectives from pediatricians

Abstract: Background and ObjectiveThe COVID-19 pandemic has led to disruptions to routine immunization programs in India and around the world, setting the stage for potentially serious outbreaks of vaccine-preventable diseases.MethodsWe surveyed pediatric healthcare providers in India in 2 rounds in April-June and September 2020 to understand how COVID-19 control measures may have impacted routine vaccination.ResultsRespondents were predominantly pediatricians working in primary, secondary or tertiary healthcare centers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Shet et al . [ 10 ] found a 50% decline in vaccination services in the month of June 2020 as reported by 83% of the 424 surveyed pediatricians. The authors also reported that 76% of the pediatricians expressed concerns about the gap in the coverage of RI.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Shet et al . [ 10 ] found a 50% decline in vaccination services in the month of June 2020 as reported by 83% of the 424 surveyed pediatricians. The authors also reported that 76% of the pediatricians expressed concerns about the gap in the coverage of RI.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In Bangladesh, 40% of mothers reported disruptions to family planning services [21][22][23]. The findings on disruptions to child vaccination programs are more consistent across countries, as many countries temporarily paused mass vaccination campaigns between March and May 2020 [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…[Rana S 2021] In India, survey data of paediatric healthcare providers from April to June and September 2020 reported a greater than 50% drop in vaccination services by 83% of the respondents in June (n=424 respondents) and 33% in September (n=141). [Shet 2021] In Indonesia, 42% (480/1137) of survey respondents reported disruption of childhood vaccination services in local health facilities and 13% (193/1137) of respondents explained that their children could not be vaccinated because a healthcare facility temporarily stopped vaccination service. Of all respondents, 312 (27%) delayed vaccinating their children for a compulsory vaccination shot.…”
Section: Asiamentioning
confidence: 99%